A high temperature and corrosion resistant sensor gas chamber and preparation method thereof

By using low-carbon stainless steel substrates and multi-layer optical reinforced coatings, the problem of degradation in traditional gas sensor gas chambers in high temperature and corrosive gas environments is solved, and higher optical reflective performance and longer service life are achieved.

CN119104494BActive Publication Date: 2025-04-11SIGAS MEASUREMENT ENG CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411225967.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-03
Publication Date
2025-04-11
Estimated Expiration
2044-09-03

AI Technical Summary

Technical Problem

Traditional gas sensor gas chambers are prone to oxidation and corrosion in high temperature and corrosive gas environments, resulting in a degradation of optical reflection performance and affecting detection accuracy and service life.

Method used

The gas chamber blank is prepared by low-carbon stainless steel substrate, and the connecting layer, intermediate layer and surface layer are arranged in sequence along the direction away from the gas chamber body. The connecting layer is mainly composed of chromium oxide, silicon nitride and zirconium oxide. The intermediate layer contains silver nanopowder and tantalum pentoxide, and the surface layer contains magnesium fluoride and microcapsule hafnium nitride.

Benefits of technology

At high temperatures of 100-300°C and in corrosive gas environments, the sensor gas chamber can maintain good optical reflection performance, improve detection accuracy and sensitivity, and extend service life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005024562380000121
    Figure BDA0005024562380000121
  • Figure BDA0005024562380000122
    Figure BDA0005024562380000122
Patent Text Reader

Abstract

The present application relates to the field of sensor materials, and specifically discloses a high temperature and corrosion resistant sensor air chamber and a preparation method thereof, wherein the sensor air chamber comprises an air chamber blank, and the air chamber blank comprises the following raw materials: C, Mn, Si, Ni, Cr, S, P, Mo, and the remainder is Fe; the present application also discloses its preparation method, which comprises the following steps: S1, preparing the air chamber blank: adding raw materials in proportion, smelting, pouring in a mold, cooling, solidifying and forming, and demolding to obtain the air chamber blank; S2, cleaning the surface of the air chamber blank, and then immersing the air chamber blank in a chemical polishing liquid for chemical polishing; S3, using sandpaper for physical polishing after chemical polishing; S4, cleaning and drying the inner wall after physical polishing to obtain the sensor air chamber. The present application has the characteristics of improving the thermal stability and corrosion resistance of the sensor air chamber, so that it maintains good optical reflection performance under high temperature conditions and corrosive gas conditions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of sensor materials, and more specifically, to a high temperature and corrosion resistant sensor chamber and a preparation method thereof. Background Art

[0002] With the continuous advancement of industrialization and technological development, gas sensors are increasingly used in many fields such as environmental monitoring, industrial production, medical health, etc. As an important component of the sensor, the performance of the sensor chamber directly affects the accuracy and service life of the sensor.

[0003] For example, the working principle of the commonly used reflective absorption spectroscopy gas sensor relies on the absorption and reflection of light by gas molecules. The gas chamber in the sensor is filled with the gas to be measured. When light passes through the gas chamber, the gas molecules absorb light of a specific wavelength, causing the light intensity to weaken. The light is then reflected multiple times by optical elements such as reflectors, forming a longer light path in the gas chamber to increase the interaction time between light and gas, thereby improving the detection sensitivity. Finally, by detecting the intensity change of the reflected light, the concentration of the gas to be measured can be inferred.

[0004] In gas sensors similar to those mentioned above that are based on spectral analysis or optical absorption principles, the effective use of light is a key factor in improving detection sensitivity. Therefore, the optical reflectivity of the sensor chamber is crucial to its detection work. High reflectivity means that the loss of light on the inner wall of the chamber is reduced, and more light can participate in the detection process, which can ensure that more light energy interacts with the gas to be measured, thereby increasing the intensity of the detection signal and improving the detection sensitivity.

[0005] However, the air chamber of traditional gas sensors is generally made of aluminum alloy or metal and non-metallic gold-plated materials. Aluminum alloy has good optical reflection properties and is easy to process, but its chemical properties are unstable, it is not resistant to corrosion and oxidation, and it is easily oxidized, which affects the reflectivity. The cost of metal and non-metallic gold plating is relatively high, and the gold plating process pollutes the environment.

[0006] Therefore, it is necessary to develop a new type of high-temperature and corrosion-resistant sensor chamber, which can still retain good optical reflection performance when passing through high temperature and corrosive gases such as oxygen, so as to perform more accurate and stable detection, in order to meet the application requirements of high-temperature industrial environments, chemical production sites and certain special gas detection scenarios, which put forward higher requirements on the high-temperature and corrosion resistance of the sensor chamber. Summary of the invention

[0007] In order to improve the thermal stability and corrosion resistance of the sensor air chamber so that it can maintain good optical reflection performance under high temperature and corrosive gas conditions, the present application provides a high temperature and corrosion resistant sensor air chamber and a preparation method thereof.

[0008] In the first aspect, the present application provides a high temperature and corrosion resistant sensor air chamber, adopting the following technical scheme: a high temperature and corrosion resistant sensor air chamber, comprising an air chamber blank, wherein the air chamber blank comprises the following raw materials in mass percentage: C: ≤0.15%, Mn: ≤2%, Si: ≤1%, Ni: 4-10%, Cr: 17-23%, S: ≤0.15%, P: ≤0.04%, Mo: 1-3%, and the remainder is Fe.

[0009] By adopting the above technical scheme, the sensor air chamber material in the present application uses a stainless steel substrate with a low carbon content. The low carbon content helps to improve the corrosion resistance of the material and reduce the formation of carbides, thereby improving the corrosion resistance of the air chamber. The addition of a small amount of manganese can deoxidize and desulfurize, improve the mechanical properties and corrosion resistance of steel, and the addition of silicon improves the oxidation resistance and high temperature strength of the air chamber material. The addition of molybdenum further enhances the pitting and crevice corrosion resistance. The limitation of nickel content helps to stabilize the austenite structure, increase the toughness of the material, reduce the thermal stress cracks generated when the temperature changes, and improve the corrosion resistance of the material in a reducing environment. The control of the chromium content forms a dense passivation film, thereby preventing the corrosion of the air chamber by oxygen and acid-base gases in the air chamber. Finally, through the control of the above elements, the sensor air chamber can maintain stable performance at high temperatures of 100-300°C, and resist acid and alkali corrosion. When passing through high temperatures and corrosive gases such as oxygen, it can still maintain good optical reflection performance.

[0010] Optionally, the air chamber blank comprises the following raw materials in percentage by weight:

[0011] C: 0.05-0.15%, Mn: 1-2%, Si: 0.6-1%, Ni: 5-8%, Cr: 17-23%, S: 0.08-0.15%, P: 0.01-0.04%, Mo: 1-3%, and the balance is Fe.

[0012] By adopting the above technical solution and the above ratio, the sensor air chamber has better high temperature resistance and corrosion resistance, and its optical reflection performance under high temperature and corrosive gas is better maintained.

[0013] Optionally, the high temperature and corrosion resistant sensor air chamber further comprises an optical enhancement coating, the optical enhancement coating and the air chamber blank are sequentially arranged from the inside to the outside, and the optical enhancement coating comprises a connecting layer, an intermediate layer and a surface layer sequentially arranged in a direction away from the air chamber blank;

[0014] The connecting layer is mainly made of a mixture of chromium oxide, silicon nitride, zirconium oxide, a binder and a dispersant; the middle layer is mainly made of a mixture of silver nanopowder, tantalum pentoxide, a binder and a dispersant; and the surface layer is mainly made of a mixture of magnesium fluoride and microcapsule hafnium nitride, a binder and a dispersant.

[0015] By adopting the above technical scheme, in the present application, an optical enhancement coating is also provided on the surface of the air chamber blank, and a connecting layer, an intermediate layer and a surface layer are sequentially provided in a direction away from the air chamber blank, wherein the connecting layer is mainly composed of chromium oxide, silicon nitride and zirconium oxide. Chromium oxide as a connecting layer has good bonding force with the air chamber blank, and helps to reduce the difference in thermal barrier stress between the air chamber blank and the optical enhancement coating, thereby playing a buffering role. Silicon nitride and zirconium oxide can significantly improve the high temperature resistance while improving the bonding strength with the air chamber blank, and the connecting layer can effectively block the diffusion of metal ions in the substrate to the optical enhancement coating, thereby improving the overall stability of the optical enhancement coating.

[0016] The middle layer mainly contains silver nanopowder and tantalum pentoxide. Tantalum pentoxide can significantly enhance the reflection of light, thereby improving the optical reflection performance of the coating, and it also has good stability at high temperatures. The addition of nano-metal silver particles not only helps to strengthen the bond with the connecting layer, but more importantly, the nano-silver particles can produce localized surface plasma resonance, thereby achieving high-intensity light absorption and improving reflection efficiency; finally, a coating mainly composed of magnesium fluoride and microencapsulated hafnium nitride is added to the surface layer. The addition of magnesium fluoride can form an optical interference film, which, combined with the optical performance enhancement material of the middle layer, has a certain corrosion resistance and can resist the erosion of acid, alkali and oxygen corrosive gases, ultimately significantly improving the optical reflection performance of the optical enhancement coating under corrosive gases and high temperatures.

[0017] Moreover, the addition of microcapsule hafnium nitride in the surface makes hafnium nitride not only have high reflectivity, but also have good corrosion resistance and durability. After being microencapsulated, it forms a self-healing agent. When the coating surface is slightly damaged or corroded due to high temperature or corrosion, the microcapsule ruptures and releases hafnium nitride to fill the damaged area, restoring the optical properties and integrity of the coating. Finally, the sensor chamber has better optical reflection performance in high temperature and corrosive gases.

[0018] Optionally, the microcapsule hafnium nitride includes a wall material and a core material, the core material is hafnium nitride and a polyurethane layer coated on the surface of the hafnium nitride, the wall material is epoxy resin, and the added mass ratio of the wall material to the core material is 1:(1.5-1.8).

[0019] By adopting the above technical solution, hafnium nitride is coated with a layer of polyurethane on its surface, and then epoxy resin is used as the wall material to form self-repairing microcapsules dispersed in the surface coating. In fact, when the surface is damaged by corrosion or high temperature, the core material is exposed, causing the polyurethane to solidify and the hafnium nitride to fill the damaged part, and restore the optical properties and integrity of the coating.

[0020] Optionally, the bonding layer is made of polyvinyl alcohol and epoxy resin in a mass ratio of 1:(2-3), the adhesive further includes a phenolic curing agent, and the mass ratio of the phenolic curing agent to the epoxy resin is (0.7-1):1;

[0021] The dispersant is selected from one or both of ethanol and acetone.

[0022] By adopting the above technical scheme, the adhesive in this application is epoxy resin, which forms a good interface bonding between the optical enhancement coating and the air chamber blank. It has high bonding strength and excellent high temperature resistance and corrosion resistance, while the phenolic curing agent has high heat resistance and corrosion resistance.

[0023] Optionally, the connecting layer comprises the following raw materials in parts by weight:

[0024] 10-20 parts of chromium oxide, 3-5 parts of silicon nitride, 5-8 parts of zirconium oxide, 10-20 parts of binder, 15-30 parts of dispersant;

[0025] The intermediate layer comprises the following raw materials in parts by weight: 5-12 parts of silver nanopowder, 15-25 parts of tantalum pentoxide, 8-15 parts of a binder and 15-30 parts of a dispersant;

[0026] The surface layer comprises the following raw materials in parts by weight: 8-15 parts of magnesium fluoride, 10-20 parts of microcapsule hafnium nitride, 5-10 parts of a binder and 10-20 parts of a dispersant.

[0027] By adopting the above technical solution and selecting the above-mentioned raw materials, the sensor gas chamber finally obtained still has good optical emission performance in high temperature, oxygen, acidic and alkaline gas atmosphere.

[0028] Optionally, the optical enhancement coating is prepared by the following method:

[0029] Material preparation: mixing chromium oxide, silicon nitride and zirconium oxide, adding a binder and a dispersant, and mixing to prepare a connecting layer solution;

[0030] The silver nanopowder and tantalum pentoxide are mixed, and then added into the bonding layer and the dispersant to prepare an intermediate layer solution;

[0031] Mixing magnesium fluoride powder and microcapsule hafnium nitride, adding a bonding layer and a dispersant, and mixing to obtain a surface solution;

[0032] Coating: coating the connecting layer solution on the air chamber blank, drying and solidifying it, and cooling it to room temperature; then coating the prepared intermediate layer solution on the solidified connecting layer, drying and solidifying it, and cooling it to room temperature; finally coating the prepared surface layer solution on the solidified intermediate layer, drying and solidifying it, and cooling it to room temperature to form an optical enhancement coating on the air chamber blank.

[0033] By adopting the above technical solution, in the present application, the connecting layer is dried after coating and then cured at a higher temperature, which is beneficial to enhance the bonding force between the optical enhancement coating and the air chamber blank, thereby retaining better optical reflection performance in a high-temperature corrosive gas atmosphere, improving detection accuracy and sensitivity, and extending the service life of the instrument.

[0034] Optionally, the drying parameters are: drying at 100-120° C. for 1-2 hours, and the curing parameters are: curing at 220-280° C. for 40-60 minutes after drying.

[0035] In a second aspect, the present application provides a method for preparing a high temperature and corrosion resistant sensor air chamber, which adopts the following technical solution:

[0036] A method for preparing a high temperature and corrosion resistant sensor air chamber comprises the following steps:

[0037] S1, preparing the air chamber blank: adding raw materials in proportion, melting and pouring them into a mold, cooling and solidifying them, and then demolding them to obtain the air chamber blank;

[0038] S2, cleaning the surface of the air chamber blank, and then immersing the air chamber blank in a chemical polishing liquid for chemical polishing treatment;

[0039] S3, physical polishing with sandpaper after chemical polishing;

[0040] S4. Clean and dry the inner wall after physical polishing to obtain a sensor air chamber.

[0041] By adopting the above technical scheme, the gas chamber blank in the present application is first cleaned to remove surface impurities and dirt, and then chemical polishing is used to remove microscopic unevenness on the inner wall surface to improve the surface smoothness, and then physical polishing is performed to further optimize the surface finish and ensure the parallelism and intensity of the reflected light. The polished inner wall is then cleaned and dried. The obtained gas chamber blank has excellent optical reflection properties, which is beneficial to improving the sensitivity and accuracy of gas detection.

[0042] Optionally, the chemical polishing solution in step S3 includes the following raw materials in parts by weight:

[0043] 3-5 parts of hydrogen peroxide, 60-80 parts of water, 2-5 parts of sodium silicate, 1-3 parts of trisodium phosphate, 1-3 parts of cerium oxide particles.

[0044] By adopting the above technical scheme, hydrogen peroxide is added as a strong oxidant in the present application to form an oxide film. During the process, the protruding parts of the surface of the air chamber blank dissolve faster, while the concave parts dissolve slower. The difference in solubility realizes the surface flatness, and the formed oxide film is removed by subsequent mechanical polishing, thereby making the surface smoother. Sodium silicate forms a silicate protective film to improve corrosion resistance and optical reflection performance, and trisodium phosphate acts as a buffer to stabilize the system. Sodium silicate and trisodium phosphate work together to form a protective film, which significantly improves corrosion resistance and optical properties. The addition of cerium oxide provides an efficient mechanical polishing effect and improves surface finish. In combination with hydrogen peroxide chemical polishing, the air chamber blank has good optical reflection performance after polishing, especially in high temperature and corrosive gas atmospheres. Good optical reflection performance is also maintained.

[0045] In summary, this application has the following beneficial effects:

[0046] 1. In this application, by controlling the raw materials of the air chamber blank and cooperating with subsequent physical and chemical polishing, the sensor air chamber has good optical reflection performance, and can maintain stable performance at high temperatures of 100-300°C, and is resistant to acid and alkali corrosion. When passing through high temperatures and corrosive gases such as oxygen, it can still maintain good optical reflection performance;

[0047] 2. In the present application, a connecting layer, an intermediate layer and a surface layer are sequentially arranged in a direction away from the air chamber blank. The connecting layer is mainly composed of chromium oxide, silicon nitride and zirconium oxide. Chromium oxide as a connecting layer has good bonding strength with the air chamber blank, and helps to reduce the difference in thermal barrier stress between the air chamber blank and the optical enhancement coating, playing a buffering role. Silicon nitride and zirconium oxide can significantly improve the high temperature resistance and improve the bonding strength with the air chamber blank. In addition, the connecting layer can effectively block the diffusion of metal ions in the substrate to the optical enhancement coating, thereby improving the overall stability of the optical enhancement coating.

[0048] 3. The middle layer of the optical enhancement coating of the present application mainly contains silver nanopowder and tantalum pentoxide. Tantalum pentoxide can significantly enhance the reflection of light, thereby improving the optical reflection performance of the coating, and it also has good stability at high temperatures. The addition of nano-metal silver particles not only helps to strengthen the bond with the connecting layer, but more importantly, the nano-silver particles can generate localized surface plasma resonance, thereby achieving high-intensity light absorption and improving reflection efficiency; finally, a coating mainly composed of magnesium fluoride and microcapsule hafnium nitride is added to the surface layer. The addition of magnesium fluoride can form an optical interference film, which is combined with the optical performance improvement material of the middle layer. In particular, it has certain corrosion resistance and can resist the erosion of acid, alkali and oxygen corrosive gases, and ultimately significantly improves the optical reflection performance of the optical enhancement coating under corrosive gases and high temperatures; and the addition of microcapsule hafnium nitride in the surface, hafnium nitride not only has high reflectivity, but also has good corrosion resistance and durability. After being microencapsulated, it forms a self-healing agent. When the surface of the coating is slightly damaged or corroded due to high temperature or corrosion, the microcapsule breaks and releases hafnium nitride to fill the damaged area, restoring the optical performance and integrity of the coating, and finally the sensor air chamber has better optical reflection performance in high temperature and corrosive gases. DETAILED DESCRIPTION

[0049] The present application is further described in detail below in conjunction with the examples. It is particularly noted that if no specific conditions are specified in the following examples, the experiments are carried out according to conventional conditions or the conditions recommended by the manufacturer. Unless otherwise specified, the raw materials used in the following examples can be obtained from common commercial sources.

[0050] In the following preparation examples, the epoxy resin is a bisphenol A liquid epoxy resin purchased from Shandong Shouhua Chemical Co., Ltd., with a brand of Dow Chemical and a model of DER336 337 301;

[0051] The phenolic curing agent uses T31 phenolic amine curing agent;

[0052] The polyurethane used is BASF 1164D50 polyurethane.

[0053] The following preparation example is a preparation example of microcapsule hafnium nitride

[0054] Preparation Example 1

[0055] A method for preparing microcapsule hafnium nitride comprises the following steps:

[0056] 1) Preparation of core material: firstly dissolve polyurethane in 5 times of mass of organic solvent to obtain polyurethane solution, wherein the organic solvent is a mixture of dimethylformamide and acetone in a mass ratio of 1:2;

[0057] The prepared polyurethane solution is then sprayed on the surface of the hafnium nitride particles, with the added mass ratio of polyurethane to hafnium nitride being 1:2.5; the solution is then cured at 160° C. for 40 minutes and then cooled to obtain a core material;

[0058] 2) Preparation of wall material: using bisphenol A type liquid epoxy resin as wall material and mixing it with ethanol in a mass ratio of 1:1.8 to prepare a wall material solution;

[0059] 3): Coating: spray the wall material solution prepared in step 2) onto the core material prepared in step 1), and the added mass ratio of the wall material bisphenol A type liquid epoxy resin to the core material is 1:1.6.

[0060] Preparation Example 2

[0061] A method for preparing microcapsule hafnium nitride comprises the following steps:

[0062] 1) Preparation of core material: firstly dissolve polyurethane in 4 times of mass of organic solvent to obtain polyurethane solution, wherein the organic solvent is a mixture of dimethylformamide and acetone in a mass ratio of 1:2;

[0063] Then the prepared polyurethane solution is sprayed on the surface of the hafnium nitride particles, and the added mass ratio of polyurethane to hafnium nitride is 1:2;

[0064] Then, the core material was obtained by curing at 150°C for 40 minutes and then cooling.

[0065] 2) Preparation of wall material: using bisphenol A liquid epoxy resin as the wall material and mixing it with ethanol in a mass ratio of 1:1.5 to prepare a wall material solution;

[0066] 3): Coating: spray the wall material solution prepared in step 2) onto the core material prepared in step 1), and the added mass ratio of the wall material bisphenol A type liquid epoxy resin to the core material is 1:1.5.

[0067] Preparation Example 3

[0068] A method for preparing microcapsule hafnium nitride comprises the following steps:

[0069] 1) Preparation of core material: firstly dissolving polyurethane in 6 times of mass of organic solvent to obtain polyurethane solution, wherein the organic solvent is a mixture of dimethylformamide and acetone in a mass ratio of 1:2;

[0070] Then the prepared polyurethane solution is sprayed on the surface of the hafnium nitride particles, and the added mass ratio of polyurethane to hafnium nitride is 1:3;

[0071] Then, the core material was obtained by curing at 180°C for 30 min and cooling.

[0072] 2): Prepare the wall material: use bisphenol A type liquid epoxy resin as the wall material and mix it with ethanol in a mass ratio of 1:2 to prepare a wall material solution;

[0073] 3): Coating: spray the wall material solution prepared in step 2) onto the core material prepared in step 1), and the added mass ratio of the wall material bisphenol A type liquid epoxy resin to the core material is 1:1.8.

[0074] Preparation Example 4

[0075] A method for preparing microcapsule hafnium nitride is carried out according to the method in Preparation Example 1, except that the hafnium nitride is not treated in step 1), and in step 3), the wall material solution is directly sprayed on the hafnium nitride particle core material.

[0076] Example 1

[0077] A method for preparing a high temperature and corrosion resistant sensor air chamber comprises the following steps:

[0078] S1. Preparation of air chamber blank: Prepare the raw materials according to the following mass percentages:

[0079] C: 0.1%, Mn: 1.5%, Si: 0.8%, Ni: 6%, Cr: 20%, S: 0.1%, P: 0.02%, Mo: 2%, and the balance is Fe; according to the above formula ratio, the raw materials are added into a vacuum induction melting furnace and heated to 1450°C for melting, then injected into a mold for casting, kept at 1250°C for 1.5 hours and then cooled with the furnace to obtain an air chamber casting, and then the air chamber casting is kept at 780°C for 1.5 hours for annealing, and then air-cooled to 380°C, heated to 850°C, kept for 35 minutes, and then heated to 1080°C, kept for 1.5 hours, and then water quenched and kept at 320°C for 1.5 hours and then air-cooled to obtain an air chamber blank;

[0080] S2, cleaning, degreasing and derusting the surface of the air chamber blank, and then immersing the air chamber blank in a chemical polishing liquid for chemical polishing treatment, wherein the chemical polishing liquid immerses the air chamber blank and the chemical polishing liquid is prepared by mixing the following raw materials: 4g hydrogen peroxide, 70g water, 3g sodium silicate, 2g trisodium phosphate, and 2g cerium oxide particles; the chemical polishing treatment time is 35min, and then wipe dry;

[0081] S3, physically polishing the air chamber blank after the chemical polishing treatment in step S2 using sandpaper;

[0082] S4, cleaning and drying the inner wall of the air chamber blank after being processed in step S3 to obtain a sensor air chamber.

[0083] Add raw materials in proportion, melt them, pour them into a mold, cool them, solidify them, and then demould them to obtain an air chamber blank; S2, clean the surface of the air chamber blank, and then immerse the air chamber blank in a chemical polishing liquid for chemical polishing;

[0084] S3, physical polishing with sandpaper after chemical polishing;

[0085] S4. Clean and dry the inner wall after physical polishing to obtain a sensor air chamber.

[0086] Example 2

[0087] A method for preparing a high temperature and corrosion resistant sensor air chamber comprises the following steps:

[0088] S1. Preparation of air chamber blank: Prepare the raw materials according to the following mass percentages:

[0089] C: 0.05%, Mn: 1%, Si: 0.6%, Ni: 5%, Cr: 18%, S: 0.08%, P: 0.01%, Mo: 1%, and the balance is Fe; the raw materials are added into a vacuum induction melting furnace according to the above formula ratio, heated to 1400°C for melting, then injected into a mold for casting, kept at 1200°C for 2h and then cooled with the furnace to obtain an air chamber casting, and then the air chamber casting is kept at 750°C for 2h for annealing, and then air-cooled to 350°C, heated to 800°C, kept for 40min, then heated to 1050°C, kept for 2h, then water quenched, kept at 300°C for 1h and air-cooled to obtain an air chamber blank;

[0090] S2, cleaning, degreasing and derusting the surface of the air chamber blank, and then immersing the air chamber blank in a chemical polishing liquid for chemical polishing treatment, wherein the chemical polishing liquid immerses the air chamber blank and the chemical polishing liquid is prepared by mixing the following raw materials: 3g hydrogen peroxide, 60g water, 2g sodium silicate, 1g trisodium phosphate, and 1g cerium oxide particles; the chemical polishing treatment time is 30min, and then wipe dry;

[0091] S3, physically polishing the air chamber blank after the chemical polishing treatment in step S2 using sandpaper;

[0092] S4, cleaning and drying the inner wall of the air chamber blank after being processed in step S3 to obtain a sensor air chamber.

[0093] Add raw materials in proportion, melt them, pour them into a mold, cool them, solidify them, and then demould them to obtain an air chamber blank; S2, clean the surface of the air chamber blank, and then immerse the air chamber blank in a chemical polishing liquid for chemical polishing;

[0094] S3, physical polishing with sandpaper after chemical polishing;

[0095] S4. Clean and dry the inner wall after physical polishing to obtain a sensor air chamber.

[0096] Example 3

[0097] A method for preparing a high temperature and corrosion resistant sensor air chamber comprises the following steps:

[0098] S1. Preparation of air chamber blank: Prepare the raw materials according to the following mass percentages:

[0099] C: 0.15%, Mn: 2%, Si: 1%, Ni: 8%, Cr: 20%, S: 0.15%, P: 0.04%, Mo: 3%, the balance is Fe;

[0100] The raw materials are added into a vacuum induction melting furnace according to the above formula ratio, heated to 1500°C for melting, then injected into a mold for casting, kept at 1300°C for 1 hour and then cooled with the furnace to obtain a gas chamber casting, and then the gas chamber casting is kept at 800°C for 1 hour for annealing, then air-cooled to 400°C, heated to 900°C, kept for 30 minutes, then heated to 1100°C, kept for 1 hour, then water quenched, kept at 350°C for 1 hour and then air-cooled to obtain a gas chamber blank;

[0101] S2, cleaning, degreasing and derusting the surface of the air chamber blank, and then immersing the air chamber blank in a chemical polishing liquid for chemical polishing treatment, wherein the chemical polishing liquid immerses the air chamber blank and the chemical polishing liquid is prepared by mixing the following raw materials: 5g hydrogen peroxide, 80g water, 5g sodium silicate, 3g trisodium phosphate, and 3g cerium oxide particles; the chemical polishing treatment time is 40min, and then wipe dry;

[0102] S3, physically polishing the air chamber blank after the chemical polishing treatment in step S2 using sandpaper;

[0103] S4, cleaning and drying the inner wall of the air chamber blank after being processed in step S3 to obtain a sensor air chamber.

[0104] Add raw materials in proportion, melt them, pour them into a mold, cool them, solidify them, and then demould them to obtain an air chamber blank; S2, clean the surface of the air chamber blank, and then immerse the air chamber blank in a chemical polishing liquid for chemical polishing;

[0105] S3, physical polishing with sandpaper after chemical polishing;

[0106] S4. Clean and dry the inner wall after physical polishing to obtain a sensor air chamber.

[0107] Example 4

[0108] A method for preparing a high temperature resistant and corrosion resistant sensor air chamber is carried out according to the method in Example 1, except that the raw material ratio of the air chamber blank in step S1 is as follows:

[0109] C: 0.1%, Mn: 1.5%, Si: 0.8%, Ni: 4%, Cr: 17%, S: 0.1%, P: 0.02%, Mo: 1%, and the balance is Fe.

[0110] Example 5

[0111] A method for preparing a high temperature resistant and corrosion resistant sensor air chamber is carried out according to the method in Example 1, except that the raw material ratio of the air chamber blank in step S1 is as follows:

[0112] C: 0.1%, Mn: 1.5%, Si: 0.8%, Ni: 10%, Cr: 23%, S: 0.1%, P: 0.02%, Mo: 3%, and the balance is Fe.

[0113] Example 6

[0114] A method for preparing a high temperature resistant and corrosion resistant sensor air chamber is carried out according to the method in Example 1, except that after physically polishing the air chamber in step S4, the inner wall surface of the air chamber is coated to form an optical enhancement coating. The specific operation includes the following steps:

[0115] S4-1. Prepare materials: mix 15 g of chromium oxide, 4 g of silicon nitride, and 6 g of zirconium oxide, add 15 g of a binder and 22 g of a dispersant, and mix to prepare a connecting layer solution;

[0116] 9 g of silver nanopowder (20-50 nm) and 20 g of tantalum pentoxide were mixed, and then 8 g of a bonding layer and 22 g of a dispersant were added to prepare an intermediate layer solution;

[0117] 12 g of magnesium fluoride powder and 15 g of the microcapsule hafnium nitride prepared in Preparation Example 1 were mixed, and then 8 g of a bonding layer and 15 g of a dispersant were added to prepare a surface layer solution;

[0118] The binder in the connecting layer solution, the intermediate layer solution and the surface layer solution comprises a mixture of polyvinyl alcohol and bisphenol A epoxy resin in a mass ratio of 1:2.5, acetone is selected as the dispersant, and a phenolic curing agent is added at the same time as the binder, and the mass ratio of the phenolic curing agent to the epoxy resin is 0.8:1;

[0119] S4-2, coating: coating the connecting layer solution prepared in step S4-1 on the inner wall of the air chamber blank after physical polishing, drying at 110°C for 1.5 hours, then curing at 260°C for 50 minutes, and cooling to room temperature to form a connecting layer with a thickness of 0.2 mm; then coating the prepared intermediate layer solution on the cured connecting layer, drying at 110°C for 1.5 hours, then curing at 250°C for 50 minutes, and cooling to room temperature to form an intermediate layer with a thickness of 0.1 mm; finally, coating the prepared surface layer solution on the cured intermediate layer, drying at 110°C for 1.5 hours, then curing at 250°C for 50 minutes, and cooling to room temperature to form a surface layer with a thickness of 0.2 mm, and an optical enhancement coating is formed on the air chamber blank to obtain an air chamber blank, a connecting layer, an intermediate layer and a surface layer arranged in sequence from the outside to the inside.

[0120] Example 7

[0121] A method for preparing a high temperature resistant and corrosion resistant sensor air chamber is carried out according to the method in Example 1, except that after physically polishing the air chamber in step S4, the inner wall surface of the air chamber is coated to form an optical enhancement coating. The specific operation includes the following steps:

[0122] S4-1. Prepare materials: mix 10g of chromium oxide, 3g of silicon nitride, and 5g of zirconium oxide, add 10g of a binder and 15g of a dispersant, and mix to prepare a connecting layer solution;

[0123] 5 g of silver nanopowder (20-50 nm) and 15 g of tantalum pentoxide were mixed, and then 8 g of a bonding layer and 15 g of a dispersant were added to prepare an intermediate layer solution;

[0124] 8 g of magnesium fluoride powder and 10 g of the microcapsule hafnium nitride prepared in Preparation Example 2 were mixed, and then 5 g of a bonding layer and 10 g of a dispersant were added to prepare a surface layer solution;

[0125] The binder in the connecting layer solution, the intermediate layer solution and the surface layer solution comprises a mixture of polyvinyl alcohol and bisphenol A epoxy resin in a mass ratio of 1:2, acetone is selected as the dispersant, and a phenolic curing agent is added at the same time as the binder, and the mass ratio of the phenolic curing agent to the epoxy resin is 0.7:1;

[0126] S4-2, coating: coating the connecting layer solution prepared in step S4-1 on the inner wall of the air chamber blank after physical polishing, drying at 100°C for 2h, then curing at 220°C for 60min, and cooling to room temperature to form a connecting layer with a thickness of 0.2mm; then coating the prepared intermediate layer solution on the cured connecting layer, drying at 100°C for 2h, then curing at 220°C for 60min, and cooling to room temperature to form an intermediate layer with a thickness of 0.1mm; finally, coating the prepared surface layer solution on the cured intermediate layer, drying at 100°C for 2h, then curing at 220°C for 60min, and cooling to room temperature to form a bottom layer with a thickness of 0.2mm, and an optical enhancement coating is formed on the air chamber blank to obtain an air chamber blank, a connecting layer, an intermediate layer and a surface layer arranged in sequence from the outside to the inside.

[0127] Example 8

[0128] A method for preparing a high temperature resistant and corrosion resistant sensor air chamber is carried out according to the method in Example 1, except that after physically polishing the air chamber in step S4, the inner wall surface of the air chamber is coated to form an optical enhancement coating. The specific operation includes the following steps:

[0129] S4-1. Prepare materials: mix 20g of chromium oxide, 5g of silicon nitride, and 8g of zirconium oxide, add 20g of a binder and 30g of a dispersant, and mix to prepare a connecting layer solution;

[0130] 12 g of silver nanopowder (20-50 nm) and 25 g of tantalum pentoxide were mixed, and then 15 g of a bonding layer and 30 g of a dispersant were added to prepare an intermediate layer solution;

[0131] 15 g of magnesium fluoride powder and 20 g of the microcapsule hafnium nitride prepared in Preparation Example 3 were mixed, and then 10 g of a bonding layer and 20 g of a dispersant were added to prepare a surface layer solution;

[0132] The binder in the connecting layer solution, the intermediate layer solution and the surface layer solution comprises a mixture of polyvinyl alcohol and bisphenol A epoxy resin in a mass ratio of 1:3, acetone is selected as the dispersant, and a phenolic curing agent is added at the same time as the binder, and the mass ratio of the phenolic curing agent to the epoxy resin is 1:1;

[0133] S4-2, coating: coating the connecting layer solution prepared in step S4-1 on the inner wall of the air chamber blank after physical polishing, drying at 120°C for 1h, then curing at 280°C for 40min, and cooling to room temperature to form a connecting layer with a thickness of 0.2mm; then coating the prepared intermediate layer solution on the cured connecting layer, drying at 120°C for 1h, then curing at 280°C for 40min, and cooling to room temperature to form an intermediate layer with a thickness of 0.1mm; finally, coating the prepared surface layer solution on the cured intermediate layer, drying at 100°C for 2h, then curing at 220°C for 60min, and cooling to room temperature to form a bottom layer with a thickness of 0.2mm, and an optical enhancement coating is formed on the air chamber blank to obtain an air chamber blank, a connecting layer, an intermediate layer and a surface layer arranged in sequence from the outside to the inside.

[0134] Example 9

[0135] A method for preparing a high temperature resistant and corrosion resistant sensor air chamber is carried out according to the method in Example 6, except that the microcapsule hafnium nitride in step S4-1 is the microcapsule hafnium nitride prepared in Preparation Example 4.

[0136] Example 10

[0137] A method for preparing a high temperature resistant and corrosion resistant sensor air chamber is carried out according to the method in Example 6, except that the microcapsule hafnium nitride in step S4-1 is replaced with an equal amount of hafnium nitride.

[0138] Embodiment 11

[0139] A method for preparing a high temperature resistant and corrosion resistant sensor air chamber is carried out according to the method in Example 6, except that in step S4, no connecting layer is coated, and an intermediate layer is directly coated on the air chamber blank.

[0140] Example 12

[0141] A method for preparing a high temperature resistant and corrosion resistant sensor air chamber is carried out according to the method in Example 6, except that no bottom layer coating is performed in step S4, and the sensor air chamber is directly obtained after coating the intermediate layer on the air chamber blank.

[0142] Comparative Example 1

[0143] A method for preparing a high temperature resistant and corrosion resistant sensor air chamber is carried out according to the method in Example 1, except that the chemical polishing treatment in step S2 is not performed, and the physical polishing in step S3 is directly performed.

[0144] Comparative Example 2

[0145] A method for preparing a high temperature resistant and corrosion resistant sensor air chamber is carried out according to the method in Example 1, except that sodium silicate is not added to the chemical polishing liquid in step S2.

[0146] Comparative Example 3

[0147] A method for preparing a high temperature resistant and corrosion resistant sensor air chamber is carried out according to the method in Example 1, except that cerium oxide is not added to the chemical polishing liquid in step S2.

[0148] Performance Testing

[0149] The reflectivity (under infrared light) of the inner wall of the sensor chamber prepared in the above embodiments and comparative examples was detected by a spectrometer at room temperature and pressure. Then, the sensor chamber was placed in a 300°C environment, and oxygen, sulfur dioxide and ammonia were injected into the chamber respectively. After being placed under the above conditions for 30 minutes, the reflectivity (under infrared light) was detected. The reflectivity at room temperature and pressure was used as a reference, and the reflectivity decrease rate after gas injection in a high temperature environment of 300°C was calculated. The statistical results are shown in Table 1 below.

[0150] Table 1:

[0151]

[0152] Table 1 continued:

[0153]

[0154] Referring to the test results in Table 1 above, the sensor chamber prepared in the present application still retains good optical reflection performance after being subjected to high temperature, oxygen, and acidic and alkaline gases, which is more conducive to gas detection accuracy and sensitivity. Referring to the test results of Example 1 and Comparative Example 1 above, when the chamber blank is only physically polished without chemical polishing, its optical reflection performance under high temperature corrosion conditions is significantly reduced. Combined with the test results of Comparative Examples 2 and 3, when sodium silicate or cerium oxide is not added to the chemical polishing liquid, the optical reflection performance of the prepared sensor chamber in a high temperature, oxygen and other corrosive gas environment is also significantly reduced.

[0155] Referring to the test results of Example 1 and Examples 6-8, it can be seen that when the inner wall of the sensor chamber is coated with an optical enhancement coating, the optical reflection performance of the sensor chamber in high temperature and corrosive gas is significantly improved. Combined with the test results of Example 9, when the microcapsule hafnium nitride is directly microencapsulated with hafnium nitride without being coated with an intermediate polyurethane layer, its optical reflection performance is also reduced. The hafnium nitride is first coated with polyurethane and then microencapsulated. When the coating is damaged by high temperature and corrosive gas, the microcapsule is damaged, and the hafnium nitride repairs the damaged part under the action of polyurethane, thereby improving the optical reflection performance. Referring to the test results of Example 10, In Example 10, when the surface hafnium nitride is not microencapsulated, its optical reflection performance is slightly reduced. Although hafnium nitride itself can improve the optical reflection performance of the gas chamber, in the high-temperature corrosive gas atmosphere, the coating is damaged, resulting in a reduction in its optical reflection performance. Combined with the test results of Example 11 and Example 12, it can be seen that when the inner layer of the gas chamber blank is directly coated with only the optical enhancement substance, its optical reflection performance in the high temperature and corrosive gas atmosphere is reduced compared with Example 6. The high temperature resistance and corrosion resistance of the sensor gas chamber are further improved by combining different coatings, and a high optical reflection performance is still retained in the high temperature and corrosive gas environment.

[0156] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A high temperature and corrosion resistant sensor chamber, characterized in that: The invention comprises an air chamber blank, wherein the air chamber blank comprises the following raw materials in percentage by weight: C:≤0.15%, Mn:≤2%, Si:≤1%, Ni:4-10%, Cr:17-23%, S:≤0.15%, P:≤0.04%, Mo:1-3%, the balance is Fe; The high temperature and corrosion resistant sensor air chamber further comprises an optical enhancement coating formed on the inner surface of the air chamber blank, wherein the optical enhancement coating comprises a connection layer, an intermediate layer and a surface layer sequentially arranged in a direction away from the air chamber blank; The connecting layer is made of chromium oxide, silicon nitride, zirconium oxide, a binder and a dispersant, the middle layer is made of silver nanopowder, tantalum pentoxide, a binder and a dispersant, and the surface layer is made of magnesium fluoride and microcapsule hafnium nitride, a binder and a dispersant. The microcapsule hafnium nitride comprises a wall material and a core material. The core material is hafnium nitride and a polyurethane layer coated on the surface of the hafnium nitride. The wall material is epoxy resin. The added mass ratio of the wall material to the core material is 1:(1.5-1.8).

2. A high temperature and corrosion resistant sensor chamber according to claim 1, characterized in that: The air chamber blank comprises the following raw materials in percentage by weight: C: 0.05-0.15%, Mn: 1-2%, Si: 0.6-1%, Ni: 5-8%, Cr: 18-20%, S: 0.08-0.15%, P: 0.01-0.04%, Mo: 1-3%, and the balance is Fe.

3. The high temperature and corrosion resistant sensor chamber according to claim 1, characterized in that: The adhesive in the connecting layer, the middle layer and the surface layer is selected from polyvinyl alcohol and epoxy resin in a mass ratio of 1: (2-3), and the adhesive also includes a phenolic curing agent, and the mass ratio of the phenolic curing agent to the epoxy resin is (0.7-1): 1; The dispersants in the connecting layer, the middle layer and the surface layer are selected from one or both of ethanol and acetone.

4. The high temperature and corrosion resistant sensor chamber according to claim 1, characterized in that: The connecting layer comprises the following raw materials in parts by weight: 10-20 parts of chromium oxide, 3-5 parts of silicon nitride, 5-8 parts of zirconium oxide, 10-20 parts of binder and 15-30 parts of dispersant; The intermediate layer comprises the following raw materials in parts by weight: 5-12 parts of silver nanopowder, 15-25 parts of tantalum pentoxide, 8-15 parts of a binder and 15-30 parts of a dispersant; The surface layer comprises the following raw materials in parts by weight: 8-15 parts of magnesium fluoride and 10-20 parts of microcapsule hafnium nitride, 5-10 parts of binder and 10-20 parts of dispersant.

5. The high temperature and corrosion resistant sensor chamber according to claim 1, characterized in that: The optical enhancement coating is prepared by the following process: Material preparation: chromium oxide, silicon nitride and zirconium oxide are mixed, and then a binder and a dispersant are added to prepare a connecting layer solution; Mixing silver nanopowder and tantalum pentoxide, adding a binder and a dispersant, and mixing to prepare an intermediate layer solution; Mixing magnesium fluoride powder and microcapsule hafnium nitride, adding a binder and a dispersant, and mixing to obtain a surface solution; Coating: coating the connecting layer solution on the air chamber blank, drying and solidifying it, and cooling it to room temperature; then coating the prepared intermediate layer solution on the solidified connecting layer, drying and solidifying it, and cooling it to room temperature; finally coating the prepared surface layer solution on the solidified intermediate layer, drying and solidifying it, and cooling it to room temperature to form an optical enhancement coating on the air chamber blank.

6. The high temperature and corrosion resistant sensor chamber according to claim 5, characterized in that: The drying parameters are: drying at 100-120°C for 1-2 hours, and the curing parameters are: curing at 220-280°C for 40-60 minutes after drying.

7. A method for preparing a high temperature and corrosion resistant sensor chamber as claimed in claim 1, characterized in that: The following steps are involved: S1, preparing the air chamber blank: adding raw materials in proportion, melting and pouring them into a mold, cooling and solidifying them, and then demolding them to obtain the air chamber blank; S2, cleaning the surface of the air chamber blank, and then immersing the air chamber blank in a chemical polishing liquid for chemical polishing treatment; S3, physical polishing with sandpaper after chemical polishing; S4. Clean and dry the inner wall after physical polishing to obtain a sensor air chamber.

8. The method for preparing a high temperature and corrosion resistant sensor air chamber according to claim 7, characterized in that: The chemical polishing solution in step S2 includes the following raw materials in parts by weight: 3-5 parts of hydrogen peroxide, 60-80 parts of water, 2-5 parts of sodium silicate, 1-3 parts of trisodium phosphate and 1-3 parts of cerium oxide particles.

Citation Information

Patent Citations

  • Gas sensor

    CN110914678A